DSP based implementation of adaptive speed controller for three-phase induction motor - Jing, L.; Mekhilef, Saad (2008)
In this paper, a simple adaptive speed control for induction motor is described and implemented using dedicated Digital Signal Processor (DSP). The controller structure design is based on voltage/frequency (V/Hz) control scheme that transforms the three phase motor speed into voltage and generating input of sine wave of PWM. Using these voltage components, the AC induction motor can be handled in the similar way with that of DC motor. Hence, the motor control system consists of voltage control loop and PWM control loop. To realize the speed controller, the speed reference is calculated as the output of speed sensor. From the experimental results it is shown that the overall induction motor speed control system gives good transient and the steady state responses tracks the motion profile given to the system.